Hibiscus Flower and Olive Leaf Extracts Activate Apoptosis in SH-SY5Y Cells - Elda Chiaino; Matteo Micucci; Roberta Budriesi; Laura Beatrice Mattioli; Carla Marzetti; Maddalena Corsini; Maria Frosini (MDPI AG, 2021)
Compounds of natural origin may constitute an interesting tool for the treatment of neuroblastoma, the most prevalent extracranial solid tumor in children. PRES is a commercially available food supplement, composed of a 13:2 (w/w) extracts mix of Olea europaea L. leaves (OE) and Hibiscus sabdariffa L. flowers (HS). Its potential towards neuroblastoma is still unexplored and was thus investigated in human neuroblastoma SH-SY5Y cells. PRES decreased the viability of cells in a concentration-dependent fashion (24 h IC50 247.2 ± 31.8 µg/mL). Cytotoxicity was accompanied by an increase in early and late apoptotic cells (AV-PI assay) and sub G0/G1 cells (cell cycle analysis), ROS formation, reduction in mitochondrial membrane potential, and caspases activities. The ROS scavenger N-acetyl-L-cysteine reverted the cytotoxic effects of PRES, suggesting a key role played by ROS in PRES-mediated SH-SY5Y cell death. Finally, the effects of OE and HS extracts were singularly tested and compared to those of the corresponding mixture. OE- or HS-mediated cytotoxicity was always significantly lower than that caused by PRES, suggesting a synergic effect. In conclusion, the present findings highlight the potential of PRES for the treatment of neuroblastoma and offers the basis for a further characterization of the mechanisms underlying its effects.